2011
DOI: 10.1002/ajim.20960
|View full text |Cite
|
Sign up to set email alerts
|

Improving agricultural injury surveillance: A comparison of incidence and type of injury event among three data sources

Abstract: Ambulance reports and hospital data contribute a large number of additional farm injury cases to existing surveillance data. From these cases, horse injuries, falls, and hand tool injuries appear to play a larger role in farm injuries. Future research should explore how to best use these electronic resources for agricultural injury surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 40 publications
4
25
0
Order By: Relevance
“…New York researchers identified that newspapers were needed as one of four sources to sustain a surveillance programme, and the team also found that Fatality Assessment and Control Evaluation Program contacts use death certificates and newspapers (digital and print) as their primary data sources 17. Additionally, the national gap was further emphasised through a review of the NIOSH AgFF research programme.…”
Section: Introductionmentioning
confidence: 99%
“…New York researchers identified that newspapers were needed as one of four sources to sustain a surveillance programme, and the team also found that Fatality Assessment and Control Evaluation Program contacts use death certificates and newspapers (digital and print) as their primary data sources 17. Additionally, the national gap was further emphasised through a review of the NIOSH AgFF research programme.…”
Section: Introductionmentioning
confidence: 99%
“…previous surveillance methods using the similar PCR data in hardcopy form. 27 When our surveillance system is tested in each new state, additional keywords are retained or added, to constrict the parameters in which we search. This process will continue to increase the sensitivity and specificity of the keyword method, while at the same time reducing the staff time needed for visual review.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Traditionally used for quality assurance and quality control by the Bureau of EMS, a patient care report (PCR) includes two fields of interest for farming and logging injuries: (1) a location field that allows the EMS provider to select from a list that includes "farm" and (2) a narrative field for the EMS provider to enter anything that could not be documented in another part of the PCR. In New Hampshire, EMS providers may enter the narrative by typing in a text box, or they may choose to create a narrative by answering a series of questions in separate text boxes that are then combined to create the narrative.…”
Section: Ems Datamentioning
confidence: 99%
See 1 more Smart Citation
“…First, previous research 23 showed that active surveillance can capture injury events that are not identified in PCR or hospital records therefore would be missed by a fully electronic system. However, active surveillance is a costly and time-consuming endeavor.…”
Section: Limitationsmentioning
confidence: 99%